The pathology of failed McKee-Farrar implants: correlation with modern metal-on-metal-implant failure - Munemoto, M; Grammatopoulos, G; Tanaka, Y; Gibbons, M; Athanasou, N (Springer, 2017)
The McKee-Farrar (MF) prosthesis was the first widely used total hip replacement (THR) to employ a metal-on-metal (MoM) articulation. These implants had a high rate of early aseptic loosening but a number achieved good long-term implant survival, stimulating the reintroduction of second and third generation implants of this type. In this study we analysed archival histopathology of periprosthetic tissues in twenty cases of MF aseptic implant failure to determine if there was evidence of an innate and adaptive immune response similar to that seen in modern MoM implants. The presence of macrophages, the extent of necrosis and the ALVAL response were graded semi-quantitatively. Variable but in most cases extensive tissue necrosis was associated with a heavy macrophage response to Cobalt-Chrome (Co-Cr) wear particles in periprosthetic tissues; most cases also contained evidence of a predominantly lymphocyte response which in eight cases was moderate or heavy (Oxford Grade 2/3). Our findings show that inflammatory and necrotic changes to deposition of Co-Cr wear particles are found in periprosthetic tissues of failed MF implants, indicating that there is an innate and adaptive response similar to that noted in second/third generation MoM implants; they also suggest that the pathobiological response to metal wear particles is likely to have contributed to MF implant failure in these cases.